Pengaruh Orientalis Goldziher dalam Studi Hadis Kontemporer di Indonesia - Ade Pahrudin (Refleksi, 2021)
Goldziher is considered a pioneer of skeptical hadith studies among western and non-Muslim scholars. In addition to being widely followed, his thesis received refutation and rebuttal from western scholars themselves and contemporary Muslim scholars. This study aims to determine the influence of Goldziher's hadith thought in the developments of hadith studies in Indonesia and how the responses shown by hadith researchers to his thoughts. This research is a literature study whose main data source is e-articles of religious scientific journals in Indonesia. The results of this study indicate that there are 22 articles discussing the thought of Goldziher's hadith. This shows a fairly dominant and significant influence of Goldziher's hadith thought in the dynamics of contemporary orientalist hadith studies in Indonesia. The responses shown by Indonesian hadith scholars to Goldziher's hadith thought, can be categorized into four categories; Descriptive-Exploratory, (6 articles), Descriptive-Appreciative (2 articles), Descriptive-Comparative (12 articles) and Descriptive-Comparative-negative (2 articles). This response from the hadith reviewers in Indonesia can be a trigger for the process of synthesizing a new theory from the anti-theses of Goldziher's hadith thought and those who oppose it that still not clear from the hadith researchers in Indonesia.